Wear analysis of piston ring / Muhammad Ridzuwan Tukimin ...[et al.] - Tukimin, Muhammad Ridzuwan; Zakaria, Zaidihafizi; Mahmood, Nazli (2002)
These projects were carried out because we want to know the materials that were used to make a piston ring. In this project, we also will know the type and the effect that happen to piston rings. From this project also, we will learn from the metallurgical aspect how the microstructure and hardness change when heat is applied to the materials. After doing this project, we know that metallurgy and automotive are relevant to each other. This is because, all the materials that we want to use, we have to analyze the microstructure for the suitable one or the part of the automotive did not have the characteristic of situation.